2015
DOI: 10.1007/s00277-015-2547-0
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine improves progression-free survival in older high-risk MDS patients with multiple autosomal monosomies: results of a subgroup analysis of the randomized phase III study 06011 of the EORTC Leukemia Cooperative Group and German MDS Study Group

Abstract: In a study of elderly AML patients treated with the hypomethylating agent decitabine (DAC), we noted a surprisingly favorable outcome in the (usually very unfavorable) subgroup with two or more autosomal monosomies (MK2+) within a complex karyotype (Lübbert et al., Haematologica 97:393-401, 2012

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 31 publications
(44 reference statements)
3
44
0
Order By: Relevance
“…The question of whether MK represents an independent prognostic factor of survival has been a focus of attention with many studies devoted to the subject. MK has been reported as a poor prognostic indicator in the whole patient population [1720], as well as in patients treated with HMAs [21,22]. However, Valcárcel et al reported that the prognostic value of MK is the result of its strong association with a number of chromosomal abnormalities [23]; our study supports this finding by showing that in the context of CK, MK loses its prognostic significance.…”
Section: Discussionsupporting
confidence: 85%
“…The question of whether MK represents an independent prognostic factor of survival has been a focus of attention with many studies devoted to the subject. MK has been reported as a poor prognostic indicator in the whole patient population [1720], as well as in patients treated with HMAs [21,22]. However, Valcárcel et al reported that the prognostic value of MK is the result of its strong association with a number of chromosomal abnormalities [23]; our study supports this finding by showing that in the context of CK, MK loses its prognostic significance.…”
Section: Discussionsupporting
confidence: 85%
“…23 Similarly, in patients with higher-risk MDS and monosomal karyotype treated with a hypomethylating agent, the CR rate was low (17%) and overall survival remained short (7 months). 34 The fact that lenalidomide does not act on stem cells but only on progenitors may provide a possible explanation for the early relapses observed despite the achievement of a CR. 35 The postremission strategy with low-intensity chemotherapy combined with lenalidomide that we used was possibly suboptimal in this situation, suggesting that a high or intermediate dose of AraC combined with lenalidomide should be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Decitabine (FDA-approved in 2006 for MDS) is not my first choice in patients with intermediate-2 and high risk MDS mainly due to the lack of a phase 3, randomized-controlled trial showing a clear survival benefit. 2729 The exact for reason for this is unknown but some have proposed that the current dosing strategies may favor cytotoxic effects over DNMT inhibitory effects, 30 the ideal dose/schedule has not been determined, 31,32 and the fact that decitabine has a different mechanism of action as it only incorporates into DNA, while azacitidine incorporates into both DNA and RNA. 33 Overall, decitabine is thought to have similar rates of progression-free survival and hematologic responses compared with azacitidine in retrospective studies but may be associated with slightly more neutropenic/infectious complications especially in an older patient population.…”
Section: Introductionmentioning
confidence: 99%